PERSEPSI PRODUSEN HOME INDUSTRI BIDANG PANGAN TERHADAP PENERAPAN SISTEM JAMINAN HALAL DI KOTA MATARAM - Nurul Farikhatir Rizkiyah (LPSDI Bina Patria, 2022)
This study aims to: (1) analyze the perception of Home Industry producers and (2) analyze the implementation of the Halal Assurance System on Home Industry Products in the Food Sector. This research is a qualitative research. The research sources used in this study were the LPPOM MUI of West Nusa Tenggara Province, the Department of Cooperatives in the City of Mataram and 6 producers of Home Industry in the Food Sector in the City of Mataram. The results showed that: (1) home industry producers in the food sector in the city of Mataram already know and understand the definition of halal food, the principles of criteria in the HAS and consider it important to the halalness of a food in their products; and (2) the high interest of producers in applying for halal certificates to LPPOM MUI should be balanced with socialization regarding the processing of halal certificates from LPPOM MUI to producers in the regions so that the halal food industry can be more easily realized, both in big cities and in regions.